Penerapan Culturally Responsive Teaching dalam Model Pembelajaran Discovery Learning untuk Meningkatkan Pemahaman Zat Aditif dan Adiktif - Ismi Aryanti Khusnul Khatimah; Novi Ratna Dewi; Etik Zusnaningsih (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
This study aims to improve the understanding of the concept of additives and addictive substances in class IX D students of SMPN 11 Semarang through the application of Culturally Responsive Teaching in the Discovery Learning learning model. This study is a Classroom Action Research (CAR) conducted in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were 32 class IX D students, consisting of 16 males and 16 females. Data collection techniques were carried out through learning outcome tests, observations and student response questionnaires. The results showed that the application of Culturally Responsive Teaching in Discovery Learning was able to improve students' understanding of the concept of additives and addictive substances. The average student score increased from 44.06 in the pre-cycle with 12.50% completion, to 64.53 with 46.88% completion in cycle I, to 80.16 with 93.75% completion in cycle II. In addition to improving learning outcomes, there was also an increase in student participation in discussions and exploration of concepts in learning. Thus, the application of Culturally Responsive Teaching in Discovery Learning has proven effective in improving the understanding of the concept of additive and addictive substances.